Factors influence employee engagement leveraging by organisational culture (pilot study in Libyan banking sector) - McLaughlin, Patrick; Al-Ashaab, Ahmed; Rashid, Hamad (Scientific Journals International (SJI), 2017)
The concept of organizational culture has been a subject of growing interest among many scholars owing to its impact in promoting engagement and organisational performance. Yet it still lacks sufficient application in the Arab world where sociocultural dynamics based on Islam tend to be unique in comparison to the western world. In Libya, this has been further complicated by the ongoing instability and volatile political climate that followed the fall of Gadhafi regime. This proof-of-concept study considered employee and managerial perceptions on the organisational culture promoting engagement in four Libyan banks. Specifically, it discusses the disparities between employee and managerial assessment of the key constraints to engagement and organisational culture at the workplace. The study identifies eleven areas of interest for the Libyan banks that are of concern including cooperation, corruption, experience, health, leadership, motivation, nepotism, teamwork, technology, training, and trust. The findings will be used to formulate new theory, determine key research themes, and refine the research agenda for an extended study.
Keywords: Employee engagement; Organisational culture